2021
DOI: 10.3390/ijms22169057
|View full text |Cite
|
Sign up to set email alerts
|

Iterated Virtual Screening-Assisted Antiviral and Enzyme Inhibition Assays Reveal the Discovery of Novel Promising Anti-SARS-CoV-2 with Dual Activity

Abstract: Unfortunately, COVID-19 is still a threat to humankind and has a dramatic impact on human health, social life, the world economy, and food security. With the limited number of suggested therapies under clinical trials, the discovery of novel therapeutic agents is essential. Here, a previously identified anti-SARS-CoV-2 compound named Compound 13 (1,2,5-Oxadiazole-3-carboximidic acid, 4,4’-(methylenediimino) bis,bis[[(2-hydroxyphenyl)methylene]hydrazide) was subjected to an iterated virtual screening against SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Only M-pro inhibitors that have pIC 50 values and can inhibit SARS-CoV-2 replication in a cellular antiviral assay were included. The compound with the CAS number 339096-59-2, also named compound M3 [ 101 ], was obtained from the optimization of a previous SARS-CoV-2 M-pro inhibitor, named compound 13 [ 102 ]. Compound 339096-59-2 inhibited the SARS-CoV-2 M-pro in vitro with an IC 50 of 13 nM and displayed anti-SARS-CoV-2 activity in Vero-E6 cells infected with SARS-CoV-2 [ 101 ].…”
Section: Sars-cov-2 M-pro Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only M-pro inhibitors that have pIC 50 values and can inhibit SARS-CoV-2 replication in a cellular antiviral assay were included. The compound with the CAS number 339096-59-2, also named compound M3 [ 101 ], was obtained from the optimization of a previous SARS-CoV-2 M-pro inhibitor, named compound 13 [ 102 ]. Compound 339096-59-2 inhibited the SARS-CoV-2 M-pro in vitro with an IC 50 of 13 nM and displayed anti-SARS-CoV-2 activity in Vero-E6 cells infected with SARS-CoV-2 [ 101 ].…”
Section: Sars-cov-2 M-pro Inhibitorsmentioning
confidence: 99%
“…Compound 339096-59-2 inhibited the SARS-CoV-2 M-pro in vitro with an IC 50 of 13 nM and displayed anti-SARS-CoV-2 activity in Vero-E6 cells infected with SARS-CoV-2 [ 101 ]. The EC 50 value was 16 nM [ 101 ]. This compound also inhibited in vitro human TMPRSS2 and furin enzymes, which are required for viral entry [ 101 ].…”
Section: Sars-cov-2 M-pro Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure-activity relationships (SAR) of the most potent and selective compounds (5b, 5e, 5i, 5k and 5l) were studied using the R-group analysis tool [13]. This analysis showed that the different structural substitution resulted in a variance in the biological activity and binding affinity.…”
Section: R-group Analysismentioning
confidence: 99%
“…Structure-based virtual screening (SBVS) of diverse ligand databases, many of them containing drug repurposing candidates and natural products, has been extensively applied to identify potential 3CL pro inhibitors (Wu C. et al, 2020;Chowdhury et al, 2020;Jukic et al, 2020;Meyer-Almes, 2020;Olubiyi et al, 2020;Selvaraj et al, 2020;Federico et al, 2021;Gogoi et al, 2021;Guedes et al, 2021;Kumar et al, 2021;Lokhande et al, 2021;Naik et al, 2021;Rajpoot et al, 2021;Rehman et al, 2021;Sisakht et al, 2021). In several cases, this approach has led to the successful identification of compounds displaying in vitro inhibitory activity against 3CL pro (Ghahremanpour et al, 2020;Gupta et al, 2020;Jin et al, 2020;Li et al, 2020;Alves et al, 2021;Banerjee et al, 2021;Gunther et al, 2021;Guo et al, 2021;Gupta et al, 2021;Hamdy et al, 2021;Pathak et al, 2021;Yang et al, 2021). On the other hand, protein-peptide docking remains far more challenging compared to other small molecules due to the higher flexibility of peptides (Rentzsch and Renard, 2015;Ciemny et al, 2018;Hashemi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%